MOTIVAÇÕES PARA USO DO INSTAGRAM:: Uma adaptação e validação da escala Sheldon e Bryant ao contexto Brasileiro - Floriano, Mikaela Daiane Prestes; Silva, Andressa Hennig (Gestão e Sociedade, 2023)
This study aims to translate, cross-cultural adaptation and validation of the Motivation Scale for Instagram use, developed by Sheldon and Bryant (2016), for the Brazilian context. Therefore, the methodology of cross-cultural adaptation suggested by Beaton et al. (2000), the stages of translation, synthesis, retranslation, evaluation by an expert committee, equivalence pre-test and evaluation by the instrument's development committee. For the statistical validation of the scale, an online survey was carried out with 317 Instagram users, using the final version of the translated questionnaire. To analyze the validity of the instrument, a Confirmatory Factor Analysis was performed, using the maximum likelihood evaluation method and the covariance matrix for data entry. The results show that the aforementioned scale has adequate reliability indices for use in Brazil, and can be used in future studies in different areas of knowledge.